Pariwisata Jember dari Masa Kolonial Hingga Kontemporer - Sanjoyo, Mawardi Purbo (Prodi Pendidikan Sejarah Fakultas Keguruan dan Ilmu Pendidikan Universitas Islam Sumatera, 2024)
During the Dutch colonial era, Jember emerged as a prominent plantation area in Java, attracting significant investment from European private companies and a sizable European workforce. Despite their demanding roles in the plantation industry, Europeans frequently indulged in leisure activities across Jember, exploring its beaches, mountains, and forests. The burgeoning tourism sector was facilitated by the presence of accommodation and transportation infrastructure. Remarkably, colonial-era tourism sites continue to thrive, underscoring the enduring appeal of Jember's attractions. Various historical sources, including advertisements, newspapers, and guidebooks, offer fascinating insights into tourists' experiences. Historical research employing methods such as heuristics, criticism, interpretation, and historiography reveals that Jember's tourism traces date back to the 14th century, resurging in the 19th century with the advent of European trading airlines. The convergence of plantation agriculture and tourism has spurred infrastructure and economic development in the region, with colonial-era accommodations and attractions retaining their allure today.